Systems parasitology: effects of Fasciola hepatica on the neurochemical profile in the rat brain - Jasmina Saric; Jia V Li; Jürg Utzinger; Yulan Wang; Jennifer Keiser; Stephan Dirnhofer; Olaf Beckonert; Mansour T A Sharabiani; Judith M Fonville; Jeremy K Nicholson; Elaine Holmes (Molecular Systems Biology)
Abstract We characterize the integrated response of a rat host to the liver fluke Fasciola hepatica using a combination of 1H nuclear magnetic resonance spectroscopic profiles (liver, kidney, intestine, brain, spleen, plasma, urine, feces) and multiplex cytokine markers of systemic inflammation. Multivariate mathematical models were built to describe the main features of the infection at the systems level. In addition to the expected modulation of hepatic choline and energy metabolism, we found significant perturbations of the nucleotide balance in the brain, together with increased plasma IL‐13, suggesting a shift toward modulation of immune reactions to minimize inflammatory damage, which may favor the co‐existence of the parasite in the host. Subsequent analysis of brain extracts from other trematode infection models (i.e. Schistosoma mansoni, and Echinostoma caproni) did not elicit a change in neural nucleotide levels, indicating that the neural effects of F. hepatica infection are specific. We propose that the topographically extended response to invasion of the host as characterized by the modulated global metabolic phenotype is stratified across several bio‐organizational levels and reflects the direct manipulation of host–nucleotide balance.